The role of disruptive technology in enhancing organizational culture, transformational leadership, organizational learning, and individual readiness for change: A study on Bank Jago - P, Agung Kresnamurti Rivai; Usman, Osly; Hardini, Inkreswari Retno; Kasofi, Adnan (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the influence of disruptive technology on organizational culture, transformational leadership, organizational learning, and individual readiness for change (IRFC) in the context of a fully digital banking transformation at Bank Jago. Utilizing a quantitative research design, data were collected through a structured questionnaire distributed to 387 employees with permanent status and over five years of experience. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The findings reveal that disruptive technology significantly and positively affects organizational culture, transformational leadership, and organizational learning. These three variables, in turn, mediate the effect of disruptive technology on IRFC. Organizational learning emerges as the strongest mediator in enhancing employees’ adaptability to digital change. The study concludes that disruptive technology not only transforms operational practices but also necessitates cultural and leadership shifts to ensure successful change adoption. Practical implications highlight the importance for digital banks to invest in leadership development, continuous learning initiatives, and adaptive organizational practices. These efforts are essential to increase employee readiness and reduce resistance to ongoing technological innovation in the banking sector.